The Effect of Posture Training Support Orthosis on Static Balance in Elderly Patients with Spinal Hyperkyphosis - Fatemeh Azadinia; Mojtaba Kamyab; Hamid Behtash; Reza Vaheb Kashani; Masoud Ramin Mirzazadeh Javaheri (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2012)
Background & Objective: Falls in the elderly are common and are associated with appreciable morbidity and mortality. Hyperkyphosis is a risk factor for balance impairment and postural instability. Increased forward curvature of the spine displaces the center of mass anteriorly out of the limits of stability, and thus increases the likelihood of loss of balance and predisposes persons to fall. The orthoses are an option for decreasing the risk of falling in elderly population; however, the quantitative evidence to support their application is not convincing. The purpose of this study is to analyze the effects of posture training support orthosis on static balance of elderly people with spinal hyperkyphosis.Subjects and Methods: Eighteen elderly people with the mean age of 65.96 ± 4.4 who had thoracic kyphosis of ≥ 50 (cobb angle) were enrolled in the study. Subjects were randomly allocated into either posture training support (PTS) orthosis or control group. Patients were randomly subjected to computerized dynamic posturography, which contained sensory organization tests and limits of stability. The tests for each person was conducted in two conditions: while wearing and without wearing the orthosis, and the order of testing for each patient was randomized.Results:Wearing PTS orthosis significantly increased balance score (p<0.0001), directional control (p=0.023) and reaction time(p=0.045). In addition, significant difference in balance score (p<0.0001) and directional control (p=0.041) was observed between two groups (PTS orthosis and control group).Conclusion:The PTS orthosis improves balance in elderly people with spinal hyperkyphosis. Improved balance could reduce the risk of falls and direct and indirect costs of falls and related fractures.